2015
DOI: 10.1074/jbc.m115.637132
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Mutations Differentially Affect the Catalytic Activities of the Human B12-processing Chaperone CblC and Increase Futile Redox Cycling

Abstract: Background: CblC processes cobalamins entering a cell to a common intermediate. Results:Pathogenic mutations at Arg-161 weaken glutathione binding to CblC and stabilize cob(II)alamin. Conclusion: The R161Q/G mutations impair the dealkylation but not the decyanation activity of CblC. Significance: Increased redox cycling by the CblC mutants explains the observed cellular oxidative stress associated with this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 51 publications
1
38
0
Order By: Relevance
“…Another observation in this study is both of these pathogenic variants do not significantly affect the decyanation activity, and the authors suggested that individuals with these pathogenic variants might respond to cyanocobalamin. 28 The mild clinical and biochemical phenotype associated with the c.482G>A (p.Arg161Gln) pathogenic variant could be explained by findings in these two studies, including intermediate stability of the mutant protein and the stabilization by an increase in cobalamin concentration. Moreover, Learner-Ellis et al showed higher expression of the c.482G>A(p.Arg161Gln) mutant protein compared to the c.271dupA (p.Arg91LysfsX14) pathogenic variant 12 .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Another observation in this study is both of these pathogenic variants do not significantly affect the decyanation activity, and the authors suggested that individuals with these pathogenic variants might respond to cyanocobalamin. 28 The mild clinical and biochemical phenotype associated with the c.482G>A (p.Arg161Gln) pathogenic variant could be explained by findings in these two studies, including intermediate stability of the mutant protein and the stabilization by an increase in cobalamin concentration. Moreover, Learner-Ellis et al showed higher expression of the c.482G>A(p.Arg161Gln) mutant protein compared to the c.271dupA (p.Arg91LysfsX14) pathogenic variant 12 .…”
Section: Discussionmentioning
confidence: 91%
“…This residue is located in a cavity near the corrin ring and does not make direct contact with cobalamin 28,29 . It has been proposed that this arginine residue is important for binding of glutathione 29 , with glutathione serving as an electron donor in the dealkylation reaction of adenosylcobalamin and methylcobalamin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme was first identified for its ability to reduce TNT (Bryant et al, 1991), but homologues have since been discovered with other activities including BluB and iodotyrosine deiodinase (Bang et al, 2012; Gherasim et al, 2015; Thomas et al, 2009; Yu et al, 2012). These raise the question of how the NR fold is able to support distinct activities in different exemplars, and of how NR is able to specialize in two-electron reduction yet apply this reactivity to diverse substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The thiol oxidase activity of hCblC is muted in contrast to that of ceCblC. Interestingly, two pathological mutants of hCblC, R161Q and R161G, exhibit elevated thiol oxidase activity, which, in turn, is correlated with increased oxidative stress that is associated with the CblC disorder (14).…”
mentioning
confidence: 99%